ANALISIS PENERAPAN AKUNTANSI SYARIAH BERDASARKAN PSAK 102 PADA PEMBIAYAAN MURABAHAH DI PT. BANK BNI SYARIAH CABANG MAKASSAR - Astika, Sri; Suarni, Agusdiwana (Jurnal Ar-Ribh, 2018)
This study is to determine the suitability of the implementation of murabahah financing at PT. Bank BNI Syariah Makassar Branch with PSAK 102. This research is included in the type of quantitative research using the 2016 financial statement analysis method. The results show that the application of Islamic accounting based on PSAK 102 on murabahah financing in PT Bank BNI Syariah Makassar Branch in 2016, there are ten categories to be a comparison, namely the bank only provides murabahah financing by order, the bank only applies tough payments, the money is recognized as an amount received and recognized as a deduction of receivables, If the bank gets a discount from a third party ) then reducing the cost and recording the discount obtained is not recorded separately. If the murabahah contract does not exceed one year, the gain is recognized when the murabahah assets are delivered. If the murabahah contract exceeds one year, the benefits are categorized based on the level of risk. In terms of disclosure must be in accordance with PSAK 102 concerning Presentation of Sharia Financial Statements, however, the cost of the murabahah inventory is not disclosed in detail. Murabahah receivables will be presented at the net realized value, namely the murabahah receivables balance will be deducted from the allowance for receivables losses. Deferred murabahah margin is presented as a deduction for murabahah receivables.Keywords: Islamic accounting, PSAK 102, murabahah